Sex-Gender Comparisons in Comorbidities of Children and Adolescents With High-Functioning Autism Spectrum Disorder - Margari, Lucia; Palumbi, Roberto; Peschechera, Antonia; Craig, Francesco; de Giambattista, Concetta; Ventura, Patrizia; Margari, Francesco (Frontiers in Psychiatry, 2019)
Over the last few years, new studies focused their attention on the gender-related features in high-functioning autism spectrum disorder (HFA), often leading to controversial results. Another interesting aspect of these subtype of patients is linked to the complexity of clinical presentation, where besides core symptoms, other co-occurrence disorders may complicate the diagnostic evaluation. Therefore, we retrospectively studied 159 HFA patients, male and female, investigating their comorbidities and to find any gender difference. For each patient, were evaluated the presence/absence, type and gender distribution of psychopathological comorbidities, according to DSM-5 diagnostic criteria. The total sample was divided in 100 male and 59 female patients, age and intelligence quotient matched. In our sample, the psychiatric comorbidities observed were Attention Deficit Hyperactivity Disorder, Anxiety Disorders, Depressive Disorders, Bipolar Disorder, Obsessive-Compulsive Disorder and Anorexia Nervosa. No statistical significant differences were found between male and female HFA patients comorbidities except for Anorexia Nervosa. In both male and female patients, attention deficit and hyperactivity disorder and anxiety disorders were found in high percentage. In conclusion, our investigation showed that a statistical significant difference of comorbidity between male and female HFA patients was found only for AN diagnosis. However, the question about the distinction between female and male HFA patients remains quite interesting and an open area of research for future studies.